Response of farmland reptiles to agricultural intensification: Collapse of the common adder Vipera berus and the western green lizard Lacerta bilineata in a hedgerow landscape. (28th May 2022) - Guiller, G.; Legentilhomme, J.; Boissinot, A.; Blouin‐Demers, G.; Barbraud, C.; Lourdais, O.
Abstract: Agricultural landscapes cover a large portion of the planet and the intensification of farming is a primary cause of biodiversity loss. Changes in agricultural practices have been particularly marked in Western Europe over the last century. Hedgerow landscapes consist of complex mosaics of pastures, ponds, and hedges connected with forest patches that are favourable for biodiversity. Recently, however, these traditional farming landscapes have been profoundly simplified with a massive reduction in hedgerows. Reptiles are currently facing an important global decline, but the impact of the intensification of agricultural practices on their populations remains understudied. We studied the common European adder Vipera berus and the western green lizard Lacerta bilineata in Western France in a hedgerow landscape undergoing agricultural intensification. We first quantified the habitat changes (density of hedgerows and forest edges) from 1950 to 2015. Second, we documented changes in the distribution of V. berus and L. bilineata in the area between two surveys conducted 18 years apart (survey 1: 1994–1997 and survey 2: 2012–2015). The two species were more likely to be found at sites with dense hedgerows and forest edges at the first survey. We detected marked range contractions in the distributions of both species over 18 years (92% and 74%, respectively, for V. berus and L. bilineata ). Population monitoring of the adder with capture‐mark‐recapture at two sites revealed marked declines related to the degradation of hedgerows and closure of the forest patches. Our results underline the importance of traditional agricultural landscapes for biodiversity conservation and the value of squamate reptiles as indicator speciesed in such landscapes. Abstract : The intensification of farming is a primary cause of biodiversity loss. The impact of land use on farmland reptiles, however, remains understudied. We quantified changes in density of hedgerows and forest edges between 1950 and 2015 in western France. We documented massive declines in two initially common reptiles in the study area. Squamate reptiles can be valuable indicators of traditional agricultural landscape changes. Copyright of the photograph: Hervé Cubizolle.